Do Interest-Free Financial Organizations Offer Fair Prices to Their Customers? - Abdullah Mesut Uçar (İktisat Politikası Araştırmaları Dergisi)
This study seeks to observe whether or not the financial instruments offered by the interest-free financial institutions cause a dilemma in generating fair prices for the consumers. Additionally, it also attempts to provide a comparative framework towards cost-free and accessible financial offers in terms of loaning by both conventional and participation banks. As part of the study, a 34-item questionnaire has been drafted to identify the consumer behaviors within the framework of a theory of fair consumer behavior. To test the validity and reliability of the scale, exploratory factor analysis and cronbach alfa tests were utilized. Based on the findings in the test, 28 items were included in the analysis. Subsequently, multiple regression analysis was performed between four factors identified in conjunction with the exploratory factor analysis. The results confirm the hypotheses offered for the theory of fair consumer behavior. In other words, the study concludes that the interest-free financial institutions, serving as alternatives to the interest-based financial system, attract the fair financial system perceptions of the consumers not just because they offer interest-free products and services, but also because of additional factors.